2011
DOI: 10.1503/cjs.008210
|View full text |Cite
|
Sign up to set email alerts
|

Deep wound infection following pediatric scoliosis surgery: incidence and analysis of risk factors

Abstract: Background:Deep wound infection after spinal surgery is a severe complication that often requires prolonged medical and surgical management. It can compromise the outcome of the deformity correction, especially in patients requiring surgical intervention with subsequent removal of implants. Ascertaining the incidence and risk factors leading to infection may help to prevent this problem. Methods:We reviewed the hospital charts of all patients who underwent spinal deformity correction from 1996 to 2005. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 33 publications
5
43
0
Order By: Relevance
“…P ropionibacterium species are often grown on culture of specimens obtained at the time of orthopaedic revision surgery. The pathogenicity of this organism has been demonstrated for patients who have undergone shoulder implant surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14] , hip or knee arthroplasty [15][16][17][18][19][20][21][22] , or spine surgery [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . While many cases of Propionibacterium infections are attributed to Propionibacterium acnes, other species of Propionibacterium have been recovered from revision surgical sites 38 .…”
Section: Discussionmentioning
confidence: 99%
“…P ropionibacterium species are often grown on culture of specimens obtained at the time of orthopaedic revision surgery. The pathogenicity of this organism has been demonstrated for patients who have undergone shoulder implant surgery [1][2][3][4][5][6][7][8][9][10][11][12][13][14] , hip or knee arthroplasty [15][16][17][18][19][20][21][22] , or spine surgery [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] . While many cases of Propionibacterium infections are attributed to Propionibacterium acnes, other species of Propionibacterium have been recovered from revision surgical sites 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular patients were more likely to have an ASA score greater than 2 [35]. Similarly, Aleissa et al found a significantly higher risk of infection in patients with non-idiopathic diagnoses who had undergone spinal fusion for scoliosis [11]. Sponseller et al demonstrated that degree of cognitive impairment was a significant risk factor for deep SSI after scoliosis surgery in patients with cerebral palsy and myelodysplasia.…”
Section: Patient-related Risk Factorsmentioning
confidence: 97%
“…None of the neuromuscular patients who received autograft bone alone developed an infection, whereas 18% of the neuromuscular patients who received allograft bone developed an infection. The authors postulated that host defenses may be overwhelmed by the presence of a large amount of devitalized bone in patients who are already relatively immunocompromised [11]. In contrast, Master et al did not find that use of allograft bone correlated with increased risk of deep SSI in the neuromuscular population [8].…”
Section: Surgery-related Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations